Maximizing Performance and Sustainability in Thermal Power Generation with DCS Control - Kumar Yegireddy, Narendra; M N , V S S Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The thermal power plant relies on the initial heating of feed water to produce steam, which in turn propels the turbine. This turbine is linked to a generator, generating electricity for various applications. Any residual steam is then condensed and cycled back into the boiler, a fundamental process commonly referred to as the Rankine cycle. The central objective of this initiative is to devise an automated control system catering to critical components like the boiler, furnace, deaerator, cooling tower, turbine, feed water tank, economizer, and superheater. This system is geared towards delivering prompt responses to variations in load demands. Emphasis is also placed on improving boiler efficiency through the real-time monitoring and regulation of dynamic parameters including temperature, pressure, level, and flow. The primary goal of managing the thermal power plant is to enhance overall steam production, ensuring that efficiency and safety integrity levels are maintained at all times. The execution of this project relies on the utilization of a distributed control system (DCS). The creation of the piping and instrumentation diagram is facilitated through the application Edraw Max. This comprehensive software tool aids in the visualization and development of the project, ensuring accuracy and clarity in the planning and implementation process.